Desenvolvimento de modelo experimental de mielorradiculopatia esquistossomótica - Carvalho, Tiago Pinheiro Vaz de (2014)
Schistosomalmyeloradiculopathy (SMR) is a severe formofpresentationof schistosomiasis, in whichthe spinal cord isaffectedby species ofSchistosoma. Thisstudy aimed todevelopan animal modelof SRMcaused byS.mansoni, and characterize the sensory and motorchanges causedby the depositionofeggsof S. mansoniin the spinal cordand correlate thesensory aspects, engines and histologicalanimalsinfunction of time.Heldmechanicalsensitivitytests, behavioral and subsequenteuthanasiain two series(infected and control)animalsdividedinto six groups offivemale Wistar ratseachin5, 10, 20 and 30dayspost-infection. The experimental groupswere anaesthetizedwith halothane andinjected witha suspension ofS. mansonieggs in thesubarachnoid space.Control animalsunderwent the sameprocedure, but with phosphate buffersolution administration(PBS). The spinal cordwas removed,subjected tohistologicalanalysis ofT10and L5. It was observedreduction in surfacemechanical sensitivity, thermal sensitivityand muscle strengthcaused by theeggsof S. mansoniin the spinal cord; Changesobservedin nervous tissueof 25% of the animals following infectionof S. mansoni. The modelproved to besuitable forevaluation offunctional changesin ratsand may beuseful forpathogenesisstudiesofMRE.